Symbiotic efficiency of selected indigenous Bradyrhizobium japonicum strains - Branka Komesarović; Sulejman Redžepović; Mihaela Blažinkov; Aleksandra Sudarić; Darko Uher; Sanja Sikora (Mljekarstvo)
Symbiotic nitrogen fixation has a unique role in a sustainable agriculture because the utilization of this natural process enables significant reduction of mineral nitrogen fertilization. Thereby, selection of highly efficient symbiotic nitrogen fixators is of great importance for successful legume inoculation due to the fact that the strains of nodule bacteria strongly differ in their symbiotic efficiency, competitiveness and compatibility. The main aim of the present study was to evaluate the symbiotic characteristics of indigenous and reference Bradyrhizobium japonicum and Bradyrhizobium elkanii strains and their compatibility with different soybean cultivars in agroecological conditions of eastern Slavonia. During two years of investigations, twofactorial field trials were set up in a randomized complete block design with five replicates. The results obtained in this study show that all B. japonicum strains had positive effect on all analyzed properties and particularly on seed yield as the most important parameter in soybean production. The highest values for nodule dry weight were obtained by application of indigenous B.japonicum strain S69 that was isolated from the similar agroecologicalconditions. Although the application of B. elkanii strain S76T resulted in the most abundant nodulation, at the same time it induced chlorosis on leaves in full blossom stage. Regarding the tested soybean cultivars, Ika and Nada, significant differences in nodulation were determined. Considerable rainfall deficiency in 2002 had strong influence on all tested properties. The highest nitrogen content in soybean aerial parts as well as the seed yield were determined in application of indigenous B. japonicum strains S69 and S75. The obtained results suggest that these two indigenous strains can becharacterized as the most efficient ones and could be used for soybean inoculant production for that region.